An evaluation of the Bugallon Municipal Library towards the formulation of a development plan - Espinoza, Eugene Jose T.; Lapuz, Elvira B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This research is an evaluative study of the Bugallon Municipal Library at Bugallon, Pangasinan. The research studied and evaluated the present situation of the Bugallon Municipal Public Library through its: 1) present location and structure; 2) collection; 3) its resources; 4) personnel; 5) its facilities and equipment; and 6) its present services.
The standards set for public libraries was also checked, particularly the 1988 PLAI Proposed Minimum Standards for Public Libraries, The Provision set by The National Library, RA 7743 and its Implementing Rules and Regulations and the 'Guidelines for the Establishment and Operation of a Public Library' prepared by the Makati Municipal Library were used as basis for the study. The views and opinions of the users and the community were also solicited as means for evaluation and determining the appropriate information, education and communication needs and services of the community.
The study employed structured interview with the librarian, structured survey questionnaires for the library users and the community, document review and researches and personal visits. It was found out that Bugallon is still a Fourth-Class Municipality, but also a developing town. It is an agricultural town, but the library has few collections regarding this subject matter-it should have additional materials regarding this subject matter. It was found out that there are aspects for the aforementioned standards the library does not comply with and needs improvement like its collection, facilities and equipment, resources and its structure. Judging also from the rating of the users and the community, the over-all rating of the library is from 60 to 70 percent. The librarian should make provision for the improvement on the aspects above-mentioned five-year development plan was formulated in order to help the Bugallon Municipal Library in its furtherance.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Public libraries -- Philippines -- Pangasinan -- Bugallon